NATIONAL ASPECTS OF STUDENTS EDUCATION OF HIGHER MEDICAL EDUCATIONAL ESTABLISHMENTS - Бульбук, О. І.; Бугерчук, О. В. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
In this article the value of national aspects is presented in education of students of higher medical educational establishments. Authors discussed the main principles and tasks on which based national education of student young people, main directions of national – educate activities in higher educational establishments. Educate measures which are conducted on the departments of the Ivano-Frankivsk national university with the purpose of forming the national world outlook of students is considered.